Growing food crops in dryland conditions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Food Crops and Drought. J Ashley. CTA -Macmillan copublication. 1999. 143 pp. ISBN 0 333 59831 8.CTA number 932. 10 credit points.